Inherent safety assessment of separation equipment in preliminary engineering phase - Ahmad, Syaza Izyanni (2015)
This paper highlights the development of new numerical approach for inherent safety assessment for separation process during the preliminary engineering stage of a typical petrochemical process lifecycle. Currently, existing inherent safety assessment technique for preliminary engineering phase did not specify the type of equipment they are applicable to as most of the methods can be used for any types of equipment generally. Aside from that, their assessment parameters are not exclusive to a certain type of unit operations. This new technique offers an inherent safety assessment focusing on chemicals safety during separation process. Parameters related to chemicals involved in separation process such as volatility, toxicity, flammability as well as explosiveness will be discussed. This technique will be constructed using logistic function which offers not only hazard assessment numerically but also graphically visualizes the effect of inherent safety parameters in designing an inherently safer process. The proposed technique can be used to effectively identify the level of hazards involved in process equipment besides highlighting the potential source of hazards in the process through numerical and graphical approach.